2012
DOI: 10.4236/wja.2012.23016
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevention in Papua New Guinea: Is It Working or Not?

Abstract: Introduction: There is a global call for structural approaches to HIV that go beyond awareness and HIV testing to approach prevention work via the social and economic drivers of the epidemic. Papua New Guinea is the epicentre of the HIV epidemic in the Pacific, with an adult prevalence rate of 0.9%. Since 2004, there has been a concerted response to HIV, with vastly increased rates of HIV testing and roll-out of antiretroviral therapy, and considerable funding for HIV prevention. Objectives: While incidence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Efforts to strengthen the availability and accessibility of HIV testing services as part of the National Strategic Plan for HIV and AIDS (Acquired Immunodeficiency Syndrome) have expanded over the years [22]. HIV testing, which includes risk reduction counselling that greatly influences one's perception of HIV acquisition and increases access to ART, has been shown to change HIV-related risk behaviours in PNG [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Efforts to strengthen the availability and accessibility of HIV testing services as part of the National Strategic Plan for HIV and AIDS (Acquired Immunodeficiency Syndrome) have expanded over the years [22]. HIV testing, which includes risk reduction counselling that greatly influences one's perception of HIV acquisition and increases access to ART, has been shown to change HIV-related risk behaviours in PNG [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It confers multiple benefits for individuals who test positive and those who test negative and encourages preventive behaviors [5,6]. Despite the significant benefits, young people remain the least likely to get an HIV test and know their HIV status [15,27]. Studies have shown that not all, particularly men willingly seek HIV testing services as a way to prevent HIV transmission and/or acquisition due to various barriers, such as individual (poor HIV/AIDS knowledge, testing availability, and unwillingness to test), social (stigma, discrimination, and lack of social support), and health service utilization (loss of trust or confidence in health workers and lack of medication, including ART) [79].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The list goes on. Along with Worth [14], the Reviews concluded that there was little direct evidence that prevention, treatment and policies have had an impact.…”
Section: Introductionmentioning
confidence: 99%